2021
DOI: 10.1111/evj.13534
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omeprazole and sucralfate on gastrointestinal injury in a fasting/NSAID model

Abstract: Background: Equine gastric ulcer syndrome (EGUS) is a common and significant cause of morbidity in horses, with a range of clinical signs, including inappetence, colic and poor performance. Hospitalised horses are exposed to factors that may induce EGUS, including fasting and nonsteroidal anti-inflammatory drug (NSAID) administration, and may be at risk for development of squamous (ESGD) and glandular gastric disease (EGGD). Prophylactic anti-ulcer medication is often prescribed for these patients, but drug se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
0
8
0
2
Order By: Relevance
“…Our data showed that women consume analgesics 19% more than men. Omeprazole is a proton-pump inhibitor used for various purposes but widely prescribed to patients on non-steroidal anti-inflammatory analgesics which helps in minimizing the risk of gastritis and ulceration induced by these analgesics ( Bishop et al, 2022 ). Hence, omeprazole has followed the prescribing pattern of the analgesic group and was consumed 29% more by females than males.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that women consume analgesics 19% more than men. Omeprazole is a proton-pump inhibitor used for various purposes but widely prescribed to patients on non-steroidal anti-inflammatory analgesics which helps in minimizing the risk of gastritis and ulceration induced by these analgesics ( Bishop et al, 2022 ). Hence, omeprazole has followed the prescribing pattern of the analgesic group and was consumed 29% more by females than males.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of gastric ulcerations was found to be less with co-administration of sucralfate than with the ranitidine/phenylbutazone and phenylbutazone-only treatment groups [ 78 ]. Another study compared the effects of sucralfate (20 mg/kg PO q8 h) and omeprazole (1 mg/kg PO q24 h) on adult horses fasted and receiving flunixin (1.1 mg/kg q12 h) for five consecutive days [ 79 ]. While equine squamous gastric ulcer disease developed in both treatment groups, overall the gastric scores were lower in the omeprazole treated group, suggesting that omeprazole is superior to sucralfate in reducing the severity of NSAID induced squamous gastric ulceration [ 79 ].…”
Section: Pathologymentioning
confidence: 99%
“…Another study compared the effects of sucralfate (20 mg/kg PO q8 h) and omeprazole (1 mg/kg PO q24 h) on adult horses fasted and receiving flunixin (1.1 mg/kg q12 h) for five consecutive days [ 79 ]. While equine squamous gastric ulcer disease developed in both treatment groups, overall the gastric scores were lower in the omeprazole treated group, suggesting that omeprazole is superior to sucralfate in reducing the severity of NSAID induced squamous gastric ulceration [ 79 ]. Horses in the sucralfate treated group also had a statistically significant increase in right dorsal colon wall thickness at the end of the NSAID treatment period, while the right dorsal colon thickness in the omeprazole treated group remained unchanged [ 79 ].…”
Section: Pathologymentioning
confidence: 99%
“…Eine weitere Studie mit 12 Fohlen mit gastroduodenalen Ulcera konnte keinen therapeutischen Unterschied zwischen Sucralfat und einem Placebo feststellen (Borne und MacAllister 1993). Bishop et al (2021) stellten eine Verschlechterung sowohl von EGGD als auch ESGD bei Pferden mit durch Futterkarenzen und NSAID-Gabe induzierten Ulzerationen trotz begleitender oraler Therapie mit Sucralfat (Dosierung: 20 mg/kg KM q. 8 h) fest.…”
Section: Diskussionunclassified
“…Das oral eingegebene Medikament hebt nachweislich den pH im Pferdemagen (Jenkins et al 1992, Merritt et al 2003, Daurio et al 1999 (Murray et al 1997, Andrews et al 1999, Sykes et al 2015b, Mason et al 2019. Jedoch konnten in der bereits oben erwähnten Studie von Bishop et al (2021) mit nur 1 mg/kg KM zwar bessere Ergebnisse als mit Sucralfat-Monotherapie erzielt, aber eine Verschlechterung der ESGD (und EGGD) unter oraler Therapie mit Omeprazol nicht verhindert werden. Speziell bei glandulären Veränderungen scheint die Dosisreduktion von Omeprazol (< 4 mg/kg KM) von Nachteil zu sein (Sykes et al 2014b(Sykes et al , 2015b.…”
Section: Diskussionunclassified